Pengaruh Literasi Keuangan, Gaya Hidup, dan Pendapatan Terhadap Pengelolaan Keuangan Mahasiswa Prodi Manajemen Universitas Labuhanbatu - Mas Dewi Harahap; Bhakti Helvy Rambe; Usmala Dewi Siregar (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the influence of financial literacy, lifestyle and income on student financial management. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 100 respondents, while the population used in this study were students of the management study program at Labuhanbatu University. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study used SPSS (Statistical Product Software Solution). Data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance tests (t-tests), simultaneous significance tests (F-tests), and determination coefficient tests (R2). The results of this study indicate that financial literacy, lifestyle and income have a positive and significant effect on student financial management both partially and simultaneously as seen from the results of the determination coefficient of 0.643. This value means that student financial management can be explained by financial literacy, lifestyle and income by 64.3%. While the remaining 35.7% is influenced by other variables not examined in this study.